Evaluasi Pelaksanaan COVID-19 di Wilayah Kerja Puskesmas Tanah Abang Jakarta - Nir Ashmah (2023)
The Indonesian government created the COVID-19 Vaccination Program for the community to overcome the transmission of COVID-19. It is hoped that the target percentage for vaccinations 1 and 2 for COVID-19 is 80% of the total population of Indonesia. The Tanah Abang District Health Center in Jakarta is one of the areas whose coverage percentage has met the target of the COVID-19 vaccination program itself, which is already 100% or more. Researchers aim to evaluate the implementation of the COVID-19 vaccination program at the Tanah Abang District Health Center in Jakarta. This study uses a qualitative method with an evaluation model approach Contex Input Process Product Outcome (CIPPO). Data was collected by means of in-depth interviews, observation, and document review. There were 5 informants in this study, 2 participants were health center staff and 3 other people were program recipients. Data were analyzed with 3 stages, namely data reduction, data presentation, and drawing conclusions. Data validity uses triangulation techniques. The results of the research showed that the implementation of the COVID-19 vaccination program was carried out according to the existing legal basis and standard operating procedures. Vaccine officers are given training and certification before carrying out vaccinations. The implementation of the COVID-19 vaccination program at the Tanah Abang Health Center covers 5 sub-districts. However, the implementation of the booster program has not been effective. It is hoped that the Government and the ranks of the Health Centers will improve the communication, education and information systems so that people want to carry out booster vaccinations such as using other social media besides Instagram so that the scope of the audience is wider and reusing banners so that all District Health Center visitors are educated about the COVID-19 booster vaccination.